Surface damage of refractory high entropy alloys subject to He irradiation - Xiong, Yaoxu; Wang, Kun; Zhao, Shijun (Journal of nuclear materials, 2024)
•Parameterized interatomic potential for describing helium-metal interactions among five different refractory metals.•Multi-principal element alloys (MPEAs) exhibit resistance to large helium bubble formation, attributed to the reduced thermodynamical driving force to form large He bubbles and the kinetically suppressed motion of He atoms.•Simulations of helium implantation demonstrate that the distribution of injected helium in MPEAs is minimally influenced by surface orientations, in contrast to the significant dependence observed in tungsten. Tungsten is a leading material considered for nuclear fusion applications. However, W usually suffers from severe surface modification under exposure to He ions generated from fusion reactions. The development of high entropy alloys provides a feasible way to overcome such vulnerabilities. Herein, we explore the response of refractory multi-principal element alloys (MPEAs), WTaTi, WTaCrV, and WTaCrVTi under He implantation and compare the results with pure W. To this end, we have parameterized the interatomic interactions between the constitutive metals and He. With the developed empirical potential, we show that the formation and binding energies of He bubbles in MPEAs are lower than those in W, suggesting a reduced thermodynamical driving force to form large He bubbles in MPEAs. Simulations of He implantation further reveal that the distribution of injected He only weakly depends on the surface orientations in MPEAs. In addition, He bubbles in MPEAs are much smaller and discretely positioned. Our results suggest superior resistance of MPEAs to surface modifications under the impact of energetic He ions, rendering them promising candidate materials for nuclear reactors.